Dayah Cot Kala dan Pendidikan Islam di Nusantara - Ilham Mirsal (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
This article discusses the development of Islamic education in Indonesian archipelagostarting from Dayah (traditional Islamic boarding school) of Cot Kala as the first Islamiceducation. Dayah plays a very significant role in the development of Islamic Educationfrom the early period of Islam entering Indonesia to the present days. Moreover, the conceptof education in dayah does not only focus on teaching material things but also covers all aspects of life. However, every period has it ebb and flow, so does dayah education system. During Dutch colonialism, dayah was impacted as the ulama (dayah leader)and santri (dayah student) was fighting in the war. Post the war, dayah was reorganized.Ulama and santri re-build dayah to be a better Islamic education institution and becomea source of reference for all element of the community. These days dayah obtains a goodplace in the community, and all elements of dayah are honored because they are seen asa source of knowledge and are able to guide people to be better.